2022
DOI: 10.1186/s12912-022-00885-3
|View full text |Cite
|
Sign up to set email alerts
|

The first COVID-19 new graduate nurses generation: findings from an Italian cross-sectional study

Abstract: Background Nursing education has been disrupted by the onset of the COronaVIrus Disease 19 (COVID-19) pandemic, potentially impacting learning experiences and perceived competencies at the time of graduation. However, the learning experiences of students since the onset of COVID-19, their perceived competences achieved and the employment status one month after graduation, have not been traced to date. Methods A cross sectional online survey measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 32 publications
(27 reference statements)
1
38
0
Order By: Relevance
“…If the supervision during the pandemic was limited, this supports the finding that competence was assessed lower. The Italian study(Palese et al, 2022) likewise confirmed the changes in nursing students' perceived competence levels due to the impact of the COVID-19 pandemic. The changes and measures taken in undergraduate education to address the impact of the COVID-19 pandemic may have influenced new graduates' perceptions of their own competence and their employment status after graduation(Palese et al, 2022).The relationship between the attributes of a nursing students' final clinical learning environment with the level of their self-assessed competence was investigated in several multi-country European studies(Kaihlanen et al, 2021;Visiers-Jiménez et al, 2021).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…If the supervision during the pandemic was limited, this supports the finding that competence was assessed lower. The Italian study(Palese et al, 2022) likewise confirmed the changes in nursing students' perceived competence levels due to the impact of the COVID-19 pandemic. The changes and measures taken in undergraduate education to address the impact of the COVID-19 pandemic may have influenced new graduates' perceptions of their own competence and their employment status after graduation(Palese et al, 2022).The relationship between the attributes of a nursing students' final clinical learning environment with the level of their self-assessed competence was investigated in several multi-country European studies(Kaihlanen et al, 2021;Visiers-Jiménez et al, 2021).…”
mentioning
confidence: 52%
“…The Italian study(Palese et al, 2022) likewise confirmed the changes in nursing students' perceived competence levels due to the impact of the COVID-19 pandemic. The changes and measures taken in undergraduate education to address the impact of the COVID-19 pandemic may have influenced new graduates' perceptions of their own competence and their employment status after graduation(Palese et al, 2022).The relationship between the attributes of a nursing students' final clinical learning environment with the level of their self-assessed competence was investigated in several multi-country European studies(Kaihlanen et al, 2021;Visiers-Jiménez et al, 2021). The contribution of the students' perceptions of their final clinical learning environment, good supervisory relationship to a better level of self-assessed competence and to the success of the transition of newly graduated nurses was highlighted(Kaihlanen et al, 2021;Visiers-Jiménez et al, 2021).…”
mentioning
confidence: 52%
“…Nonetheless, the Italian National Healthcare System (NHS) was heavily stressed by COVID-19: the price that the NHS had to pay both in terms of the number of positive virus cases and deaths among the HCWs was significant and represented a peculiarity compared to what happened in other countries [ 42 ]. Considering the increase in the intensity of care due to the selective hospitalization of patients with COVID-19 and other emergency medical or surgical conditions in 2020 and 2021 [ 43 ], the low rate of staff turnover (due to the shortage of collaborators) [ 42 ], the consequent pressure to immediately recruit new nursing graduates [ 44 ], as well as residents and even medical students for some roles, the system has shown a good level of resilience and the implementation of occupational accident prevention measures prior to this emergency has certainly helped protect healthcare workers during the pandemic, although other coping strategies may have intervened. A study on organizational resilience processes among HCWs in Switzerland in the first year of the pandemic found that the difficulties in implementing COVID guidelines and protection measures fell in the category of problematic situations associated with the development of new standards, that is, HCWs became used to new ways of working and developed new skills to perform effectively [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expectations that are sometimes unrealistic may cause sense of inadequacy and stress, and this may in turn prevent NGRNs from fully deploying their competences [ 5 , 6 ]. The COVID-19 pandemic has also brought new challenges to NGRNs by decreasing graduating students’ clinical placements opportunities [ 7 , 8 ], which may in turn affect NGRNs’ readiness to enter clinical practice and increase NGRNs’ feelings of fear, fatigue, and self-doubt [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about NGRNs’ competence have focused on the practice environment, occupational commitment, and empowerment and on NGRNs’ perceptions of self-assessed competence level during their first year after graduation [ 8 , 27 33 ]. Competence-related intervention studies [ 36 38 ] have focused on more seasoned registered nurses, but studies about interventions aimed at developing NGRNs’ professional competence and preceptors’ role in competence development are lacking.…”
Section: Introductionmentioning
confidence: 99%